TERAPI BERMAIN UNTUK MENINGKATKAN KEMAMPUAN EMOSIONAL ANAK DI SEKOLAH LUAR BIASA ( SLB ) UNTUNG TUAH SAMARINDA - Rini Ernawati; Fatma Zulaikha; Milkhatun; Pipit Feriani (Jurnal Pengabdian Masyarakat Nusantara, 2025)
Absract. Children with special needs can pursue their education at a Special Education School (SLB), which is an institution specifically designed to accommodate the needs of such children, including those who are visually impaired, hearing impaired, physically disabled, intellectually disabled, mentally disabled, and children with developmental delays. In their development, children with special needs face various challenges in emotional, social, and cognitive development. Therefore, an approach that helps them develop is necessary. One approach proven to be effective in supporting their development is play therapy. The objective of this Community Service Activity (PKM) is to address the complex issues faced by children with special needs and to enhance their fine motor skills and emotional development. The solution proposed by the PKM team is to provide play therapy activities such as clay modeling, collage, drawing, and coloring, conducted in a group play setting. The activity takes the form of group play therapy facilitated by students, with participants being all 21 children from the Special Education School (SLB Untung Tuah), who served as respondents in this activity. The results of the play therapy activity showed that out of 21 children, before the activity, 2 children felt sad and 19 children felt neutral. After the play therapy activity with clay, drawing, and collage, all 21 children felt very happy and were highly enthusiastic about communicating with their peers and the service team.